2020
DOI: 10.48550/arxiv.2008.08131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Planning and Operations of Mixed Fleets in Mobility-on-Demand Systems

Kaidi Yang,
Matthew W. Tsao,
Xin Xu
et al.

Abstract: Automated vehicles (AVs) are expected to be beneficial for Mobility-on-Demand (MoD), thanks to their ability of being globally coordinated. To facilitate the steady transition towards full autonomy, we consider the transition period of AV deployment, whereby an MoD system operates a mixed fleet of automated vehicles (AVs) and human-driven vehicles (HVs). In such systems, AVs are centrally coordinated by the operator, and the HVs might strategically respond to the coordination of AVs. We devise computationally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Third, fleet size can be imposed via hard constraints, especially in time-invariant network flow models, where the number of AVs can be estimated by multiplying the sum of the customer and rebalancing flows with travel time (45). Finally, we remark on two aspects of these constraints: First, each type of constraint can be readily generalized to mixed fleets by imposing limitations on each vehicle class (95), and second, fleet sizing represents not only an operational constraint but also a design parameter for planning studies (43,45).…”
Section: Operational Constraintsmentioning
confidence: 99%
“…Third, fleet size can be imposed via hard constraints, especially in time-invariant network flow models, where the number of AVs can be estimated by multiplying the sum of the customer and rebalancing flows with travel time (45). Finally, we remark on two aspects of these constraints: First, each type of constraint can be readily generalized to mixed fleets by imposing limitations on each vehicle class (95), and second, fleet sizing represents not only an operational constraint but also a design parameter for planning studies (43,45).…”
Section: Operational Constraintsmentioning
confidence: 99%
“…Finally, we remark two aspects. First, each type of constraints can be readily generalized to mixed fleets, by imposing limitations on each vehicle class (95). Second, fleet sizing represents not only an operational constraint, but also a design parameter for planning studies (43,45).…”
Section: Operational Constraintsmentioning
confidence: 99%
“…It showed that in some cases, there is a regime in which the platform chooses to mix AVs with human drivers to maximize its profit, while in other cases, the platform will use only human drivers or AVs depending on the relative cost of AVs. In [38], an AMoD system with a mixed fleet was modeled as a Stackelberg game where the platform serves as the leader and human-driven vehicles serve as the followers. A steady-state model was proposed to determine the planning variables, and a time-varying model was formulated to design a real-time coordination algorithm for AVs.…”
Section: Introductionmentioning
confidence: 99%